Pre-saccadic Attention (and not Arousal) modulates the Size-Eccentricity Effect - Jad Laaboudi; Anne Hillairet de Boisferon; Céline Paeye (Scientific Reports)
Abstract Peripherally located objects are often perceived to be smaller than centrally located objects. This perceptual phenomenon, known as the Size-Eccentricity Effect (SEE), is mainly due to the structural properties of the visual system and is further modulated by covert attention. In this study, we evaluated whether pre-saccadic attention could also compensate for this effect. Participants performed a judgment task where they compared a test disk of varying size, briefly presented in peripheral vision, to a reference disk appearing 450 ms later in foveal vision. When no saccade was made towards the location of the test disk, the SEE was observed. However, when participants initiated saccades about 200 ms after the test disk extinction, points of subjective equality were close to objective equality. The second experiment aimed at excluding an explanation involving non-specific arousal mechanisms, also known to enhance visual perception. Participants executed a keypress or an antisaccade instead of a saccade. The SEE disappeared only in the saccade condition, confirming the crucial role of pre-saccadic attention shifts in this SEE compensation. Therefore, pre-saccadic attention improves not only the processing of orientation, contrast and spatial frequency (as previously demonstrated), but also the processing of peripheral object size.